LEGISLATIVE MEASURES TO PREVENT AND COMBAT SEXUAL VIOLENCE AGAINST CHILD: NATIONAL AND INTERNATIONAL PERSPECTIVE - Antonius PS Wibowo (UBL, 2016)
Legislative measures is one of some measures commonly used as internationally accepted on the logical framework to ensure that implementation of the international convention at the States parties to its international convention will become appropriate. In context of implementation of the Convention on the Rights of the Child, legislative measures should be afforded by an administrative and other measures that include among others: decentralisation, federalisation and delegation; training and capacity-building; visible in budgets. Legislative measures means an active measure taken by the government and parliament to apply the best interests principle by systematically considering on the how children’s rights and interests will be affected by their actions. This may a proposal of the new law which is directly concerned with children, including those which are not directly concerned with children, but indirectly affect children. Realisation of legislative measures and administrative and other measures will assure that implementation of the international convention will become appropriate and gives an envisaged impact.Ministerial of Women Empowerment and Child Protection has applied a holistic approach to developt a child protection system. This approach consists of some elements and one of them is regulatory and policy framework (Kerangka Hukum dan Kebijakan). This is actually a legislative measures based on internationally accepted on the logical framework.Legislative measures to prevent and combat sexual violence against child consists of a proposal of the new law which is directly concerned with children, including those which are not directly concerned with children, but indirectly affect children. The first one is debate on the propose of national law on the chemical castration=hukum kebiri dengan disuntik. This is a measure to combat sexual violence against child. The second one is debate on the necessity of controling of the internet shop operation (warung internet), the necessity of proposal or implementation of law on control of liquor and alcoholic (Undang-undang tentang Pengendalian Minuman Keras dan Beralkohol) at the local/regional level (regional law/Peraturan Daerah), and the necessity of amendment and implementation of the Law on the Media (Undang-undang tentang Pers=UU Nomor 40 Tahun 1999), in particular the prohibition of publication of sadistic criminal action. These are measures to prevent sexual violence against child.